Body Composition and Physical Fitness Profile of PERSIPASI (Persatuan Sepakbola Indonesia Patriot Bekasi) U-17 Soccer Players in Bekasi City - Dani Nur Riyadi; Aridhotul Haqiyah; Ahlan Tubagus (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2025)
This study aimed to describe the body composition and physical fitness profile of PERSIPASI U-17 soccer players in Bekasi City. A descriptive quantitative design with a cross-sectional approach was used. Participants were 11 male U-17 players who were actively involved in regular training. Body composition was assessed using a Karada Scan. Physical fitness was evaluated through field tests, including push-up, sit-up, agility run, sit-and-reach, standing broad jump, endurance run, and leg strength test. Results showed that players generally had BMI values within the normal to slightly above-normal range, with inter-individual variation in body fat and skeletal muscle mass. Most players demonstrated good to excellent upper-body and abdominal strength, high flexibility, and adequate aerobic endurance. However, agility, leg power, and leg strength were predominantly in the moderate to poor categories. These findings suggest that the current training program sufficiently develops endurance and general strength but needs to be refined to more specifically target agility and explosive lower-limb performance. In conclusion, the physical profile of PERSIPASI U-17 players is characterized by favorable body composition and several strong fitness components, yet there remains substantial room for improvement in agility, leg power, and leg strength through more focused and integrated training interventions.